2004
DOI: 10.7202/007495ar
|View full text |Cite
|
Sign up to set email alerts
|

The Gender of Precarious Employment in Canada

Abstract: Summary This article examines the relationship between gender, forms of employment and dimensions of precarious employment in Canada, using data from the Labour Force Survey and the General Social Survey. Full-time permanent wage work decreased for both women and men between 1989 and 2001, but women remain more likely to be employed in part-time and temporary wage work as compared to men. Layering forms of wage work with indicators of regulatory protection, control and income results in a continuum w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(156 citation statements)
references
References 18 publications
7
142
0
7
Order By: Relevance
“…Nonetheless, some research across different countries reports that women have equal or even greater levels of overall job satisfaction compared with men (Lowe, 2007;Magee, 2013;Shields, 2006). These results have been considered paradoxical because women tend to receive fewer job-related resources than do men (Cranford, Vosko, & Zukewich, 2003;Magee, 2013;Phelan, 1994). Two possible explanations have been advanced.…”
Section: A Gender Lens On Well-being At Workmentioning
confidence: 99%
“…Nonetheless, some research across different countries reports that women have equal or even greater levels of overall job satisfaction compared with men (Lowe, 2007;Magee, 2013;Shields, 2006). These results have been considered paradoxical because women tend to receive fewer job-related resources than do men (Cranford, Vosko, & Zukewich, 2003;Magee, 2013;Phelan, 1994). Two possible explanations have been advanced.…”
Section: A Gender Lens On Well-being At Workmentioning
confidence: 99%
“…As of October 2007, 21.2% of Canadian women worked part-time compared to 6.4% of men. Women are almost twice as likely as men to be part-time temporary workers in comparison with men (Cranford, Vosko and Zukewich, 2003). The participation rates of women have experienced an upward trend since the passage of the Employment Equity Act in 1986 and several reasons have been advanced to explain this increase in participation rates.…”
Section: Labour Force Participationmentioning
confidence: 99%
“…Overall, the authors do not find any proof that women and racial minorities hired in businesses covered by affirmative action have a performance level lower than white males and this, even though the average level of education of black employees is lower. While discrimination against women appears to have declined, the research evidence indicates that Canadian women continue to face significant labour market problems (Vosko, 2000(Vosko, , 2006Cranford, Vosko and Zukewich, 2003).…”
Section: Occupational Segregation Of Womenmentioning
confidence: 99%
“…With respect to the position of temporary agency workers, this specific industrial relations system should be analyzed more thoroughly. Finally, research has indicated that some demographic groups, including women (Cranford, Vosko and Zukewich, 2003) and low skilled workers (Maurin and Postel-Vinay, 2005) are overrepresented in temporary and precarious employment. More research is needed to more explicitly assess the institutional position of these groups in the context of precarious temporary employment.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this comparison, temporary workers are generally found to be worse off compared to permanent workers (Kalleberg, 2000;McKeown, 2005). Temporary jobs are therefore regarded as a form of precarious employment, involving limited social benefits and statutory entitlements, low earnings, and poor working conditions (Cranford, Vosko, and Zukewich, 2003).…”
mentioning
confidence: 98%